The wind [videorecording (DVD)] : demons of the prairie - Tammi, Emma; Gerard, Caitlin; Telles, Julia Goldani; Zukerman, Ashley (Scream Factory, 2019)
On the nineteenth-century American frontier, a woman living with her husband in a desolate cabin experiences an increasing feeling of being surrounded by supernatural forces.